Coated cutting tool
The coating tool design with a Ti-rich intermediate film and nitride/carbide top layer addresses durability issues by enhancing adhesion and abrasion resistance, improving performance in high-speed steel cutting.
Patent Information
- Application Number
- JP2023120108
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-02-05
AI Technical Summary
Existing coating tools with intermediate films containing TiN suffer from inadequate durability, particularly in high-speed steel cutting applications.
A coating tool design featuring a substrate with a Ti-rich intermediate film layer (layer A) and a top layer (layer B) composed of nitride or carbide, where layer A has a high nitrogen content and a face-centered cubic (FCC) structure, enhancing adhesion and durability, while layer B maintains a similar structure for improved abrasion resistance.
The enhanced coating tool demonstrates improved durability and adhesion, particularly in high-speed steel cutting, with the Ti-rich layer A increasing bonding strength and layer B providing superior abrasion resistance.
Smart Images

Figure 2025017171000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to coated cutting tools, such as end mills. [Background technology]
[0002] AlCrSi nitride or carbonitride is a film type with excellent heat resistance and wear resistance, and is applied to coated cutting tools. The present inventor has proposed a coated cutting tool applicable to the milling of high-hardness steel, in which an intermediate film containing W and Ti with a face-centered cubic lattice structure is formed directly on the substrate by Ti bombardment, and an AlCrSi nitride or carbonitride with a fine film structure due to a high Si content is provided directly on the intermediate film (Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2021 / 131232 Summary of the Invention [Problem to be solved by the invention]
[0004] The coated cutting tool described in Patent Document 1 has excellent durability in cutting hard steel. However, the present inventors have confirmed that there is room for improvement in the adhesion of the intermediate coating formed by Ti bombardment. [Means for solving the problem]
[0005] According to one aspect of the present invention, there is provided a coated cutting tool having a substrate surface coated with a hard coating, the hard coating being disposed on the substrate surface, the hard coating containing W in the largest amount among metal elements including metalloids, followed by Ti in the second largest amount, the total content ratio of W and Ti being 70 atomic % or more, and the hard coating containing carbon in the largest amount among non-metal elements, followed by nitrogen in the second largest amount, and the total content ratio of metal elements including metalloids, carbon, nitrogen and oxygen being taken as 100 atomic %, with a nitrogen content ratio N A and carbon content ratio CA Ratio to N A / C A The present invention provides a coated cutting tool including: a layer A having a face-centered cubic lattice structure, with a refractive index of 0.40 or more and a film thickness of 1 nm to 20 nm; and a layer B having a face-centered cubic lattice structure and made of a nitride or a carbonitride, disposed on the layer A.
[0006] The A layer has a nitrogen content ratio N A and the total content ratio M of metal elements including metalloids A Ratio to N A / M A is preferably 0.6 or more. The B layer may be a nitride or carbonitride containing Al, Cr and Si, in which the content ratio of Al among the metal elements including metalloids is 50 atomic % or more and 65 atomic % or less, the content ratio of Cr is 20 atomic % or more and 40 atomic % or less, the total content ratio of Al and Cr is 85 atomic % or more and 96 atomic % or less, and the content ratio of Si is 4 atomic % or more and 15 atomic % or less. In this case, the B layer may be a nitride or carbonitride containing Al, Cr and Si, in which the atomic ratio M of the metal elements including metalloids when the total of the metal elements and nonmetallic elements is 100%. B and the atomic ratio of nitrogen, N B Toga 1.07 <N B / ME B <1.30 is also acceptable. The layer B may further include a layer C made of a nitride or carbonitride of a metal element including a metalloid. The C layer may be a nitride or carbonitride in which the content of Ti among metal elements including metalloids is 60 atomic % or more and 95 atomic % or less, and the content of Si is 5 atomic % or more and 40 atomic % or less. Effect of the Invention
[0007] According to one aspect of the present invention, a coated cutting tool having excellent durability is provided. [Brief description of the drawings]
[0008] [Figure 1]1 is a transmission electron microscope photograph of the cutting edge of the tool of Example 1. In the figure, point 1 indicates the substrate, point 2 indicates layer A, and point 3 indicates layer B. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The inventors have confirmed that by setting the nitrogen content of the intermediate coating by Ti bombardment to a certain level or more, the adhesion between the substrate and the hard coating is improved, and the durability of the coated cutting tool tends to be increased. Hereinafter, details of the embodiments of the present invention will be described.
[0010] The coated cutting tool of this embodiment includes a substrate, a layer A disposed on the surface of the substrate, and a layer B disposed on the layer A. In the coated cutting tool of this embodiment, the layer B is a hard coating that imparts durability to the tool. The layer A is an intermediate coating that improves adhesion between the layer B and the substrate. The substrate is a WC-based cemented carbide substrate for cutting tools. The substrate may be a solid tool with a head and a shank integrated together, a head of a head-replaceable tool, or a cutting insert to be attached to a holder.
[0011] First, the layer A, which is the intermediate film of this embodiment, will be described. The A layer is a Ti bombarded layer with a face-centered cubic lattice structure provided between the substrate and the B layer, which has a face-centered cubic lattice structure and is made of a nitride or carbonitride, as described below. By making the A layer disposed on the surface of the substrate have a face-centered cubic lattice structure (fcc structure), the B layer on the A layer can easily maintain a face-centered cubic lattice structure (fcc structure), and the crystals of the substrate, A layer, and B layer are continuous, improving adhesion. In addition, the crystallinity of the B layer in the vicinity of the boundary with the A layer is increased, which is thought to improve adhesion between the substrate and B layer. The A layer is a Ti bombarded layer, which is disposed on the surface of the substrate, and contains W most abundantly among metal elements including semimetals (hereinafter referred to as metal elements), followed by Ti, with the total content ratio of W and Ti being 70 atomic % or more (hereinafter simply referred to as %). The A layer has a stable crystal structure due to the total content ratio of W and Ti being 70% or more among the metal elements. The A layer preferably has a total content ratio of W and Ti being 75% or more.
[0012] Among nonmetallic elements, layer A contains the most carbon, followed by nitrogen. Layer A may contain oxygen and argon as nonmetallic elements other than carbon and nitrogen. When the total content ratio of metal elements, carbon, nitrogen, and oxygen is 100%, layer A has a nitrogen content ratio of N A and carbon content ratio C A Ratio to N A / C A is 0.40 or more. By containing nitrogen relative to carbon at a certain ratio or more, the adhesion with layer B is enhanced and the durability of the coated cutting tool is improved. In other words, the coated cutting tool of this embodiment improves the adhesion between layer B and the substrate by forming layer A between the substrate and layer B, which has a face-centered cubic lattice structure (fcc structure) mainly composed of W and Ti and has a high nitrogen content ratio. A / C A is preferably 0.45 or more. In addition, in order to stabilize the crystal structure of the A layer, N A / C A is preferably 0.7 or less. A / C A is preferably 0.6 or less.
[0013] The A layer is the nitrogen content ratio N when the total content ratio of metal elements, carbon, nitrogen and oxygen is 100%. A and the total content ratio of metal elements M A Ratio to N A / M A It is preferable that the ratio of nitrogen to metal elements in the A layer is more than a certain ratio, since this increases the adhesion between the A layer and the B layer. A / M A In order to stabilize the crystal structure of the A layer, NA / M A is preferably 1.0 or less. A / M A is preferably 0.9 or less.
[0014] The A layer may contain hard coating components and substrate components in addition to W and Ti. However, in order to stabilize the composition and crystal structure of the A layer, it is preferable that the total content ratio of Al and Si among the metal elements in the A layer is 15% or less. The composition and crystal structure of the A layer become more stable as the amount of Al and Si contained in the A layer decreases. It is preferable that the total content ratio of Al and Si among the metal elements in the A layer is 10% or less. The A layer is likely to contain Co and Cr contained in the binder phase of the substrate. Even if the A layer contains Co and Cr, the total content ratio of Co and Cr among the metal elements is preferably 15% or less. The A layer is preferably the total content ratio of Co and Cr among the metal elements is 10% or less. The film thickness, composition, and crystal structure of the A layer can be confirmed by cross-sectional observation using a transmission electron microscope, composition analysis, and nanobeam diffraction pattern.
[0015] If the thickness of the A layer is too thin, the adhesion to the substrate decreases. Also, if the thickness of the A layer is too large, the adhesion to the substrate tends to decrease. Therefore, the thickness of the A layer is set to 1 nm or more and 20 nm or less. The thickness of the A layer is preferably set to 2 nm or more and 15 nm or less.
[0016] Next, the layer B which is the hard coating of the present invention will be described. The B layer is a hard coating having a face-centered cubic lattice structure made of a nitride or carbonitride provided on the above-mentioned A layer. The face-centered cubic lattice structure hard coating made of a nitride or carbonitride has excellent wear resistance and heat resistance and is widely used in coated cutting tools. Among them, nitrides or carbonitrides mainly made of Al, Cr, and Ti are used in coated cutting tools, and the B layer is preferably a nitride or carbonitride containing at least one of Al, Cr, and Ti in total at 80% or more. The B layer is more preferably made of a nitride having excellent heat resistance. The B layer may be a single layer film or a laminated film in which multiple layers with different compositions are laminated. In the coated cutting tool of this embodiment, it is important that the B layer has a face-centered cubic lattice structure (fcc structure). In this embodiment, the face-centered cubic lattice structure (fcc structure) means that the diffraction intensity caused by the face-centered cubic lattice structure (fcc structure) shows the maximum intensity in X-ray diffraction. A hard coating that shows the maximum intensity of the diffraction intensity caused by the hexagonal close-packed structure (hcp structure) is brittle, and therefore has poor durability as a coated cutting tool. In particular, durability tends to decrease in wet processing. It is preferable that the B layer does not have a diffraction intensity due to a hexagonal close-packed structure (hcp structure) in X-ray diffraction. However, if the diffraction intensity due to a face-centered cubic lattice structure (fcc structure) shows the maximum intensity, the B layer may partially contain a hexagonal close-packed structure (hcp structure) and an amorphous phase.
[0017] When the test area of the coating is small or when another coating described later is coated on the B layer, it may be difficult to identify the face-centered cubic lattice structure (fcc structure) by the X-ray diffraction. Even in such a case, the crystal structure can be identified by the selected area diffraction method using a transmission electron microscope (TEM). It is preferable that the B layer does not have a peak mainly composed of hexagonal crystals in the intensity profile obtained from the selected area diffraction pattern.
[0018] The B layer is preferably an AlCrSi nitride or carbonitride, which is a film type with excellent heat resistance and wear resistance. Among them, the AlCrSi nitride or carbonitride, which has a high Si content, has a fine film structure, and the Ti bombarded layer is easily provided to improve adhesion. Therefore, the B layer is preferably a nitride or carbonitride containing Al, Cr, and Si, in which the Al content of the metal elements is 50% to 65%, the Cr content is 20% to 40%, the total content of Al and Cr is 85% to 96%, and the Si content is 4% to 15%.
[0019] In the case where the B layer is an AlCrSi nitride or carbonitride with a high Si content, the atomic ratio M of metallic elements including metalloids when the total of metallic elements and nonmetallic elements in the B layer is taken as 100% is B and the atomic ratio of nitrogen, N B Toga 1.07 <N B / M B It is preferable that the relationship <1.30 is satisfied. By applying the layer A according to the present invention to the layer B having a high nitrogen content, the effect of improving the adhesion can be easily obtained.
[0020] The composition of layer B can be measured by using an electron probe microanalyzer (EPMA) for the mirror-finished hard coating. In this case, for example, after mirror-finishing the hard coating surface, five analysis points with a diameter of about 1 μm are analyzed, and the composition can be calculated by averaging the three points excluding the maximum and minimum values.
[0021] If the thickness of the B layer is too thin, the excellent durability may not be fully exhibited. Also, if the thickness is too thick, peeling of the film may occur. The thickness of the B layer may be selected from the range of, for example, 0.5 μm or more and 10 μm or less. The thickness of the B layer is more preferably 1 μm or more. Also, the thickness of the B layer is more preferably 5 μm or less.
[0022] In this embodiment, the effect of this embodiment can be achieved even if another layer is coated on the B layer. Therefore, the coating structure consisting of the A layer and the B layer in this embodiment may adopt a configuration in which another layer is coated in addition to the configuration in which the B layer is the outermost surface of the tool. In this case, it is preferable that the B layer is coated with the C layer made of a nitride or a carbonitride having excellent heat resistance and wear resistance as a protective coating. The C layer is more preferably a layer made of a nitride. The C layer is preferably a hard coating having excellent thermal shock resistance and residual compressive stress. The composition of the C layer may be appropriately selected depending on the workpiece material and processing conditions. In particular, in wet processing, the hard coating is easily peeled off due to the heating and cooling cycle, so it is preferable to provide a hard coating having high residual compressive stress as a protective coating. As the C layer, a nitride or carbonitride having a Ti content of 60% or more and 95% or less and a Si content of 5% or more and 40% or less is preferable, in that it is a coating type having a particularly high residual compressive stress.
[0023] In order to form the A layer of this embodiment on the substrate, Ti bombardment is performed on the substrate. The deposition device used for Ti bombardment is preferably equipped with a cathode having a magnetic field configuration in which a coil magnet is arranged around the outer periphery of the target to confine the arc spot inside the target. By using such a cathode to perform bombardment with Ti, an element species that easily forms carbides, oxides on the substrate surface are removed and cleaned. In addition to this cleaning, the bombarded Ti ions diffuse into the WC on the substrate surface, making it easier to form a layer containing W and Ti. In this embodiment, the A layer containing W and Ti is formed on the cutting edge, which is the functional part, thereby improving the adhesion between the substrate and the hard coating at the cutting edge, thereby obtaining the effect of increasing the durability of the coated cutting tool. When the absolute value of the negative pressure bias voltage applied to the substrate during Ti bombardment is small and the current input to the target is low, a layer containing W and Ti is difficult to form on the substrate surface. Therefore, the negative pressure bias voltage applied to the substrate is preferably -1000V or more and -700V or less. Also, the current input to the target is preferably 80A or more and 150A or less. The temperature inside the furnace is preferably 400°C or more and 800°C or less. Ti bombardment is preferably performed by introducing nitrogen gas into a vacuum chamber at 5 to 50 sccm. According to the study by the present inventors, it has been confirmed that the thickness of layer A formed on the tool cutting edge is affected by differences in the tool diameter, cutting edge shape, and other shapes. EXAMPLES
[0024] <Base material> The substrate was a two-blade ball end mill made of cemented carbide with the composition WC (bal.)-Co (8 mass%)-Cr (0.5 mass%)-VC (0.3 mass%), with an average WC grain size of 0.6 μm and a hardness of 93.9 HRA.
[0025] <Manufacturing method> The deposition was performed using an arc ion plating system, which includes multiple cathodes (arc evaporation sources), a vacuum chamber, and a substrate rotation mechanism. The cathodes are equipped with one cathode (hereinafter referred to as "C1") with a coil magnet on the outer periphery of the target, and two cathodes (hereinafter referred to as "C2" and "C3") with permanent magnets on the back and outer periphery of the target, and a magnetic field generating coil in front of the target to generate a magnetic field to push the plasma forward. The distance from the target surface to the substrate is 400 mm. The inside of the vacuum chamber is evacuated by a vacuum pump, and gas is introduced through a supply port. A bias power supply is connected to the substrate placed in the vacuum chamber, and a negative bias voltage is applied to the substrate independently. The substrate rotation mechanism has a worktable, a plate-shaped jig on the worktable, and a pipe-shaped jig on the plate-shaped jig. The worktable rotates at a speed of 3 revolutions per minute, and the plate-shaped jig and the pipe-shaped jig each rotate on their own axes. A metal Ti target is installed at C1, an AlCrSi alloy target is installed at C2, and a TiSi alloy target is installed at C3.
[0026] <Heating and Vacuum Exhaust Process> The substrate was fixed to the pipe-shaped jig in the vacuum chamber, and the pre-film formation process was carried out as follows. First, the inside of the vacuum chamber was evacuated to a pressure of 5×10 -3 Pa or less. Then, the substrate was heated by a heater installed in the vacuum chamber until the substrate temperature reached 500°C, and vacuum evacuation was performed. As a result, the substrate temperature was set to 500°C, and the pressure inside the vacuum chamber was set to 5×10 -3 Pa or less.
[0027] <Ar Bombardment Process> After that, Ar gas was introduced into the vacuum chamber, and the pressure inside the chamber was set to 0.50 Pa. Then, a current of 30 A was supplied to the filament electrode, a negative bias voltage of -150 V was applied to the substrate, and Ar bombardment was carried out for 60 minutes.
[0028] <Ti Bombardment Process> After that, nitrogen gas was introduced into the vacuum chamber at a rate of 30 sccm, and the pressure inside the chamber was set to 0.3 Pa. Then, a current of 90 A was supplied to the metal Ti target, a negative bias voltage of -800 V was applied to the substrate, and Ti bombardment was carried out for 15 minutes.
[0029] <Film Deposition Process> After Ti bombardment, nitrogen gas was introduced into the vacuum chamber to set the pressure in the vacuum chamber to 4 Pa. A current of 100 A was supplied to the Al60Cr30Si10 target (numbers are atomic ratios; the same applies below), a current of 5 A was supplied to the magnetic field generating coil, and a negative bias voltage of -150 V was applied to the substrate to coat a hard nitride film with a thickness of approximately 2 μm. Next, a current of 150 A was supplied to the Ti75Si25 target, a current of 5 A was supplied to the magnetic field generating coil, and a negative bias voltage of -50 V was applied to the substrate to coat an upper layer of nitride with a thickness of approximately 1 μm.
[0030] In the conventional coating, Ar gas was introduced into the vacuum chamber at 30 sccm during Ti bombardment, and the pressure inside the chamber was set to 0.3 Pa. Then, a current of 90 A was supplied to the Ti target, a negative bias voltage of -800 V was applied to the substrate, and Ti bombardment was performed for 15 minutes. The conditions for forming the hard coating were the same as those for the coating of this embodiment.
[0031] To confirm the film structure of layer A, a field emission transmission electron microscope (JEM-2010F, manufactured by JEOL Ltd.) was used to observe the cross section of the cutting edge of the ball end mill. The sample was cut and attached to a dummy substrate using epoxy resin. The sample was then cut, attached with a Mo reinforcing ring, polished, dimpled, and subjected to Ar ion milling to prepare it for measurement. Carbon deposition was applied before measurement. Observation, composition analysis, and nanobeam diffraction were performed at an accelerating voltage of 200 kV. The composition of layer A was determined by energy dispersive X-ray spectroscopy (EDS). Nanobeam diffraction was performed with a camera length of 50 cm and a beam diameter of approximately 0.2 nm, and the vicinity of the center of the film thickness was analyzed. The analysis results are shown in Table 1.
[0032] [Table 1]
[0033] The composition of layer B was measured using a wavelength dispersive electron probe microanalysis (WDS-EPMA) attached to an electron probe microanalyzer (JXA-8500F, manufactured by JEOL Ltd.). The mirror-finished sample was subjected to ion beam irradiation at an accelerating voltage of 10 kV and a probe current of 5 × 10 -8 A, The acquisition time was 10 seconds, and the analysis area was an area of approximately 1 μm in diameter, with five points measured, and the average value was calculated. The average composition of the B layer is (Al56Cr33Si11)N, and N B / M B The value was 1.20. It was also confirmed that the intensity profile obtained from the selected area diffraction pattern did not have any peaks mainly due to hexagonal crystals.
[0034] (Condition) Dry processing Tool: 2-blade carbide ball end mill Model number: EPDBE2010-6, ball radius 0.5mm Cutting method: bottom cutting Work material: STAVAX (52HRC) (manufactured by BOHER-Uddeholm Co., Ltd.) Cut: Axial, 0.04mm, Radial, 0.04mm Cutting speed: 75.4m / min Feed per blade: 0.0179mm / blade Cutting distance: 15m Evaluation method: After cutting, the material was observed at a magnification of 1000x using a scanning electron microscope, and the width of the abrasion between the tool and the workpiece on the tool flank was measured. The part with the largest abrasion width was recorded as the maximum wear width on the flank.
[0035] [Table 2]
[0036] In Example 1, the A layer had a high nitrogen content and was more adhesive. In the above-mentioned examples, the B layer was made of AlCrSi nitride, which has a high Si content and tends to have a fine coating structure and poor adhesion, but even if the B layer has a different composition, the effect of improving adhesion can be achieved.
Claims
1. A coated cutting tool having a substrate having a surface coated with a hard coating, the hard coating is disposed on the surface of the substrate, contains W in the largest amount among metal elements including metalloids, followed by Ti in the second largest amount, the total content ratio of W and Ti being 70 atomic % or more, contains carbon in the largest amount among non-metal elements, followed by nitrogen in the second largest amount, When the total content ratio of metal elements including metalloids, carbon, nitrogen and oxygen is 100 atomic %, the nitrogen content ratio N A and carbon content ratio C A Ratio to N A / C A A layer A having a face-centered cubic lattice structure and a thickness of 1 nm to 20 nm, and a layer B, which is disposed on the layer A and has a face-centered cubic lattice structure and is made of a nitride or a carbonitride.
2. The A layer has a nitrogen content ratio N A and the total content ratio M of metal elements including metalloids A Ratio to N A / M A 2. The coated cutting tool according to claim 1, wherein the coefficient of friction is 0.6 or more.
3. 3. The coated cutting tool according to claim 1, wherein the B layer is a nitride or carbonitride containing Al, Cr and Si, in which, among metal elements including semi-metals, the content of Al is from 50 atomic % to 65 atomic %, the content of Cr is from 20 atomic % to 40 atomic %, the total content of Al and Cr is from 85 atomic % to 96 atomic %, and the content of Si is from 4 atomic % to 15 atomic %.
4. The B layer has an atomic ratio M of metal elements including metalloids when the total of metal elements and nonmetallic elements is 100%. B and the atomic ratio of nitrogen N B and 1.07<N B / M B The coated cutting tool according to claim 3 , which satisfies the relationship:
5. 2. The coated cutting tool according to claim 1, further comprising a layer C on the layer B, the layer C being made of a nitride or carbonitride of a metal element including a metalloid.
6. 6. The coated cutting tool according to claim 5, wherein the C layer is made of a nitride or a carbonitride having, among metal elements including semi-metals, a Ti content of 60 atomic % or more and 95 atomic % or less and a Si content of 5 atomic % or more and 40 atomic % or less.
Citation Information
Patent Citations
Coated cutting tool
WO2021131232A1
Cited By
Cutting tools
JP7907812B1